Antiseptic Resistance in Methicillin Sensitive and Methicillin Resistant Staphylococcus aureus Isolates from Some Major Hospitals, Iran - Hasanvand, Azar; Ghafourian, Sobhan; Taherikalani, Morovat; A. Jalilian, Farid; Sadeghifard, Nourkhoda; Pakzad, Iraj (Recent Patents on Anti-Infective Drug Discovery, 2015)
Background: Extensive use of antibiotics and biocide in treatment of patients and cleaning of surfaces and medical equipment has led to the emergence of resistant microorganisms. The current research goals to determine the antiseptics Minimum Inhibitory Concentration value in Staphylococcus aureus (methicillin -resistant Staphylococcus aureus and methicillin sensitive Staphylococcus aureus) isolates from some major hospitals in Iran and to detect qacA/B, norA , smr and blaZ genes. Methods: Two hundred isolates of S. aureus including 100 MRSA and 100 MSSA clinical isolates were collected from 4 hospitals in the west of Iran during period 2012 to 2013. Detection of disinfectant resistant genes (qac A/B, smr and norA), antimicrobial resistance genes (mecA and blaZ) and SCCmec typing of MRSA isolates was performed by PCR. Results: MIC of chlorhexidine digluconate (CHX) in 70% of MRSA and 30% of MSSA strains was 8-16 µg/ml. High level of MIC of citrimide (>2 µg/ml) in MRSA and MSSA isolates was 20% and 5% ,respectively. MIC of benzalkonium chloride (BC) in 80% of MRSA and 83% of MSSA isolates was less than 2µg/ml; only 9% of MRSA had MIC higher than 2µg/ml. Frequency of antiseptic and antibiotic resistance genes norA, blaZ and qacA/B in MRSA isolates were 83%, 98% and 9%, respectively; while this value for MSSA isolates were 62%, 8% and 0%, respectively. The smr gene was not detected in both MRSA and MSSA isolates. In all biocides high MIC were observed in SCCmec type III and IVc. High frequency of qacA/B gene was found in SCCmec type III,Vc and IVb, which were 66.6% ,22% and 11.1% respectively. Conclusion: We found SCCmec types III, Vc was related to high MIC of biocide in MRSA isolates.
Keywords: Iran